2007
DOI: 10.1111/j.1539-6924.2006.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Flash Flood Awareness in Southwest Virginia

Abstract: Flash floods are one of the most dangerous weather-related natural disasters in the world. These events develop less than six hours after a rainfall event and create hazardous situations for people and extensive damage to property. It is critical for flash flood conditions to be warned of in a timely manner to minimize impacts. There is currently a knowledge gap between flood experts and the general public about the level of perceived risk that the latter has toward the powerful flood waters and how events sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 11 publications
8
84
0
2
Order By: Relevance
“…This is useful for two reasons: First of all, the risk of flood induced by heavy rain is a potential danger to every household in the country. Local examples demonstrate that economic damages from these events should not be neglected (City of Copenhagen 2012; Kandilioti and Makropoulos 2012;Knocke and Kolivras 2007;Veronesi et al 2013). Secondly, many policies intended to stimulate private flood mitigation are located or debated at the national or federal state level.…”
Section: Introductionmentioning
confidence: 99%
“…This is useful for two reasons: First of all, the risk of flood induced by heavy rain is a potential danger to every household in the country. Local examples demonstrate that economic damages from these events should not be neglected (City of Copenhagen 2012; Kandilioti and Makropoulos 2012;Knocke and Kolivras 2007;Veronesi et al 2013). Secondly, many policies intended to stimulate private flood mitigation are located or debated at the national or federal state level.…”
Section: Introductionmentioning
confidence: 99%
“…Those with flood experience tend to have a greater awareness/perception of flood risk (Parker and Harding, 1979;Siegrist and Gutscher, 2006;Knocke and Kolivras, 2007;Burningham, Fielding, and Thrush, 2008;Miceli, Sotgiu, and Settanni, 2008;Botzen, Aerts, and van den Bergh, 2009;Bradford et al, 2012;Fielding, 2012;Harries, 2012;Scolobig, De Marchi, and Borga, 2012;Kellens, Terpstra, and De Maeyer, 2013). Residents with flood experience prior to flash flood events (as compared to those without) have been found to have a higher awareness of flooding and a higher perception of future flood risk (Scolobig, De Marchi, and Borga, 2012), and past experience of flooding has been found to be associated with perceived risks of flash floods (Knocke and Kolivras, 2007). Concern about flooding has been found to be correlated with past flood frequency in different areas (Prelog and Miller, 2013), and a higher frequency of floods experienced has been found to be associated with increased negative emotions and health issues owing to stress during the flood season (Hansson, Noulles, and Bellovich, 1982).…”
Section: Flood Policy Change and The Importance Of Risk Perception Rementioning
confidence: 99%
“…In addition, given the high frequency of recent summer floods in the UK, and the effect of recent policy changes, research on the ways that individuals perceive and respond to extreme flood events is vital. Further research of flash flood perceptions has been identified as important (Knocke and Kolivras, 2007;Cave et al, 2009). This paper also seeks to satisfy a recommendation for further research on associations between experience and perceptions (Kellens et al, 2013), and aims to contribute to a need for 'a re-invigoration of flood risk perception research' to understand better its relationships with 'the vulnerability, capacity and resilience of individuals and communities in the face of flooding' (Birkholz et al, 2014, p. 18).…”
Section: Flood Policy Change and The Importance Of Risk Perception Rementioning
confidence: 99%
“…A study that separated these activities into two groups, those linked to 'survival' (first aid kits, water and the like) and 'damage mitigation' (such as securing tall furniture to walls in seismic risk areas) found that the first group of actions were more commonly adopted than the second [29]. Furthermore, hazard exposure can arise from two sources: direct interaction with the threat, or indirect (vicarious) experience from media reports, or hearing vivid descriptions of others' experiences [30,31]. It is possible that the small minority of people reported as having taken anticipatory actions in the absence of any personal experience may, therefore, have been prompted by vicarious experiences.…”
Section: Past Action: Hazard Experience and Preparednessmentioning
confidence: 99%